An A-Z of pasta : recipes for shapes and sauces, from alfabeto to ziti, and everything in between - Roddy, Rachel (Alfred A. Knopf, 2023)
"This is the story of pasta. Here award-winning food writer Rachel Roddy has lived and cooked in Rome for over a decade. She has spent years browsing bucolic Italian markets, cooking with fresh and seasonal vegetables, discovering cheeses, and perfecting the art of making Italy's favorite food: pasta. Now, she has condensed everything she's learned about pasta in a practical, alphabetical, highly entertaining collection of pasta and pasta sauce recipes that will ensure authentic Italian meals and take your pasta dishes to the next level. In this cookbook, you will learn the many ways to pair pasta shapes with sauce, how to make certain pastas from scratch, and how to best serve them--from Cavatelli with Sausage, Tomato and Mint to Capelli with Shrimp. There are also short essays that weave together the history, culture and the astonishing variety of pasta shapes from the tip to the toe of Italy. Featuring the familiar favorites--pesto, ragù and carbonara--and new twists on classics, as well as tricks and techniques for maximum flavor, An A-Z of Pasta is a glorious celebration of pasta from one of the best food writers of our time"--